Recruitment Advertising: Changes Within the Last Four Decades in Sri Lanka (Vallis Aurea, 2023)
Recruitment is one of the most important functions of the Human Resource Management and the success of the function is depended on the attraction of most suitable candidates to the relevant vacancy. To attract applicants, the organizations can be used no of modes, however among those, most popular one is newspaper advertisements. However just publishing advertisement on newspaper does not bring expected results. To get maximum results, the advertisements should be prepared in an attractive way. Under this study, it was evaluated the changes happen with newspaper advertisements within last fourdecades to get understand how that advertisements has create attractively and to understand the trends of the current newspaper advertisements. For that, it has used 200 published advertisements with the period 1970 –2009 as a sample of the study. According to the results usage of graphics, company logo, pictures, have been increased. On the other hand, usage of descriptive language in recruitment advertisements has been increased. Most of recruitment advertisements presented the position in direct, however there is a trend to present in creative ways and with a statement that encourage applications.